FORMATION AND DEVELOPMENT OF HUMAN CAPITAL AND SOCIAL-LABOR RELATIONS: THE EXPERIENCE OF SINGAPORE - K. Kh. Abdurakhmanov (Стратегические решения и риск-менеджмент)
The article discusses Singapore’s experience in the formation and development of human capital and social-labor relations. Singapore's successful implementation of policies in the areas of education, health care and the development of social and industrial relations was studied. Among the four major ‘economic tigers’ of East Asia, Singapore is the undisputed leader, as evidenced by key economic indices and ratings. Singapore has steadily improved its economic performance thanks to Lee Kuan Yew’s forward-looking policies and rigorous implementation, and anticipating challenges on many fronts. The President of the Republic of Uzbekistan has identified six key areas of cooperation with Singapore in the near future, which are outlined in the article. There are great prospects for cooperation in the field of education, the development of information and telecommunications technologies, the financial and banking sectors, partnership in the areas of ‘smart nation’ and ‘digital government’ in the field of ‘smart cities,’ digital public services, fintech and artificial intelligence. In this way, Singapore has shown that investment in human capital can pay big dividends, and that nothing is impossible when it comes to technological breakthroughs in the Republic of Uzbekistan.